PERANCANGAN STANDAR OPERASIONAL PROSEDUR (SOP) DAN DOKUMEN PENJUALAN KREDIT PADA PT SINAR KOBEL INDONESIA - Ulul Azmi; Sugeng Riadi (ABEC Indonesia, 2021)
This study discusses about the design of SOP and credit sales documents at PT Sinar Kobel Indonesia. This research uses descriptive method that describes the procedure of sales activities at PT Sinar Kobel Indonesia, starting from orders from customers, making invoices, and exiting goods from warehouses, then grouping the activities and documents of credit sales. The results suggest that PT Sinar Kobel Indonesia needs to use quotation documents, purchase orders, and inventory cards as proof of a written agreement between the company and the buyer.